1974
DOI: 10.1021/ja00812a044
|View full text |Cite
|
Sign up to set email alerts
|

Thermal isomerization of 1,2-dialkenylcyclopropanes

Abstract: The etc, ett, and ttt isomers of l,2-di(prop-l'-enyl)cyclopropane isomerize at 165°at comparable rates to give, respectively, c/s,dj,dj-di(prop-l'-enyl)cyclopropane, írans-6,7-dimethylcyclohepta-l,4-diene, and cis-6,7dimethylcyclohepta-1,4-diene. These highly stereoselective and stereospecific reactions are interpreted in terms of a common mechanism involving a one-center epimerization as the rate-limiting step, followed by rapid Cope rearrangement of the trans,cis,trans-and m.ds.fra/w-dipropenylcyclopropanes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Their spontaneous [3,3]‐sigmatropic rearrangement was expected to result in the formation of cycloheptadienes 4 . The reaction was previously shown to proceed via a boat like transition state ,,. Hydrolysis of the enamine would then release the catalyst and the desired cycloheptadienals 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their spontaneous [3,3]‐sigmatropic rearrangement was expected to result in the formation of cycloheptadienes 4 . The reaction was previously shown to proceed via a boat like transition state ,,. Hydrolysis of the enamine would then release the catalyst and the desired cycloheptadienals 5 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that a Z ‐configuration within the substrates results in a significant increase of the activation barrier for the 3,3‐sigmatropic rearrangement of divinylcyclo‐propanes . Such a rearrangement usually requires higher reaction temperatures not compatible with the temperature sensitive organocatalyst (−)‐ 2 a .…”
Section: Methodsmentioning
confidence: 99%
“…The cis-divinyl cyclopropane to cycloheptadiene rearrangement profits from the release of ring strain and is a well-known variation of the Cope rearrangement [32]. An application in the total synthesis of (±)-gelsemine 16 is depicted in Scheme 5.20 [33].…”
Section: The Cope Rearrangementmentioning
confidence: 99%
“…The thermal conversion of irtfw,y-l,2-divinylcyclopropanes to cyclohepta-1,4-dienes, which occur by way of cw-l,2-divinylcyclopropanes (Ullenius et al, 1972;Baldwin and Ullenius, 1974), may involve one-center epimerizations or, conceivably, two-center epimerizations, at C(l) and C(3), or C(2) and C(3). The point has not yet been subjected to an experimental test.…”
Section: A-o Dmentioning
confidence: 99%